Investigation and analysis of color pragmatics in Beyghami DarabNameh - Bigleri Delavii, Susan (2021)
In the present article, the function of colors in Beyghami DarabNameh has been investigated by descriptive-analytical method. The most frequent colors in this prose work are black and red; the main reason for this frequency is the epic content and the occurrence of successive wars. A common function seen in all colors is the descriptive aspect. In addition, the description of the biological and psychological conditions of the characters, the induction of inner emotions and objectification of abstract concepts has been done with the help of colors. In general, the colors used in DarabNameh are non-symbolic, explicit and direct, and lack multiple layers of meaning, which indicates the realistic and objectivist attitude of the author. The most important weakness of Beyghami in the field of storytelling, which is revealed by analyzing the pragmatics of colors, is the imbalance in its application in the narrative process.